2017
DOI: 10.3390/ijms18061137
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Applications of Rose Hips from Different Rosa Species

Abstract: Rosa species, rose hips, are widespread wild plants that have been traditionally used as medicinal compounds for the treatment of a wide variety of diseases. The therapeutic potential of these plants is based on its antioxidant effects caused by or associated with its phytochemical composition, which includes ascorbic acid, phenolic compounds and healthy fatty acids among others. Over the last few years, medicinal interest in rose hips has increased as a consequence of recent research that has studied its pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 204 publications
(270 reference statements)
2
108
0
2
Order By: Relevance
“…So, taking into consideration the different mechanisms involved in these assays and their specific chemical environment, we can hypothesise that the antioxidant power of the extract from Rosa spp. stems is mainly due to water‐soluble biophenols acting with HAT mechanism . These results could be similar to those found with other food samples .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…So, taking into consideration the different mechanisms involved in these assays and their specific chemical environment, we can hypothesise that the antioxidant power of the extract from Rosa spp. stems is mainly due to water‐soluble biophenols acting with HAT mechanism . These results could be similar to those found with other food samples .…”
Section: Resultssupporting
confidence: 90%
“…stems is mainly due to water-soluble biophenols acting with HAT mechanism. 27,36 These results could be similar to those found with other food samples. 37 Prior et al 37 reported that the antioxidant capacity by ORAC assay of pine nuts, sorghum bran and strawberry was mostly attributed to their hydrophilic fractions.…”
Section: Antioxidant Activitysupporting
confidence: 90%
“…Metabolites formed from γ‐linolenic acid improve cellular membrane function, restore the skin lipid barrier, and significantly reduces inflammation through prostaglandin formation. The α‐linolenic acid, which also occurs in large quantities in rose hip seed oil, is converted in the body into other biologically active fatty acids: eicosapentaenoic and docosahexaenoic which play an important role in preventing cardiovascular health, protecting the nervous system, formation of cellular walls and oxygen uptake …”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, many underutilized oil sources have been recognized and their nutritional and safety assessment was being conducted . It seems that one of such unexploited oil source are rose hip seeds that represent a waste material during production of teas, jams, juices, and pharmaceuticals from rose hips. The rose hip, also called the fruit, is a pseudocarp or pseudo‐fructus, consisting of fleshy walls surrounding a cavity containing the seeds .…”
Section: Introductionmentioning
confidence: 99%
“…The most active component in the oil 92, 6-Dymethoxoy-4vinylphenol) acts as a potent oxidizing and nitrang agent (Wakamatsu et al, 2005). The Roship oil which in a member of used mixture is rich in phenolic compound, carotenoids, ascorbic acid, polyunsaturated fatty acids, linolenic acid, and phytosterols, mainly β-sitosterol which have antioxidant activity (İlyasoğlu and Arpa, 2017;Mármol et al, 2017).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%